Magnetic properties of two GdIIIFeIII4 metallacrowns and strategies for optimizing the magnetocaloric effect of this topology. Issue 10 (15th April 2021) - Salerno, Elvin V.; Kampf, Jeff W.; Pecoraro, Vincent L.; Mallah, Talal
Abstract : Two Gd 3+ [12-MCFe III (N)shi -4] metallacrowns are analyzed for magnetic properties, and calculations concerning the magnetic exchange parameters of this topology are considered. Abstract : Two Gd III Fe III 4 metallacrown complexes are presented and analyzed for their magnetic properties. One of these species is newly identified and exhibits a bent ring geometry as opposed to the more conventional flatter conformation of the other. Both complexes are quite similar magnetically, exhibiting antiferromagnetic exchange coupling values ca . J (Fe III –N–O–Fe III ) = −7 cm −1 and J (Gd III –O–Fe III ) = −0.7 cm −1 . When analyzed for the molecular magnetocaloric effect, maximum −Δ S m values of 7.3 J K −1 kg −1 at 3 K and at 6.1 J K −1 kg −1 at 4 K were exhibited. A detailed structural-magnetic correlation is established and an assessment of several similar magnetic metallacrowns with diverse metal combinations is given with regards to their potential magnetocaloric properties. Strategies for improving the magnetocaloric properties within the Metaln + FeIII4 family of metallacrowns are proposed regarding the ratio between coupling parameters J (Fe III –N–O–Fe III )/ J (Metal n + –O–Fe III ).